Modification of Differential Gear based on Multi-objective Optimization - Qiqi Feng; Tao Wang; Liangmo Wang; Hanguan Xia; Yi Dong; Yaozu Wang (Jixie chuandong)
In order to reduce vibration and noise， the modification of the tooth profile of the planetary gear and the eccentric helix are studied. The influence of tooth profile modification，helix modification， helix modification factorⅠand helix modification factorⅡon transmission error peak difference， tooth surface maximum contact stress， tooth root bending stress of planetary gear and tooth root bending stress of half-shaft gear are analyzed respectively by KISSSoft. The regression equations of four response quantities are established by Minitab， and the optimal modification scheme is obtained under the condition of minimum transmission error peak difference， minimum contact stress on the tooth surface and the bending stress at the tooth root of the planetary gear is no more than 1 100 MPa. After modification， the peak difference of transmission error is reduced by 11.39%， the maximum contact stress of tooth surface is reduced by 3.89% and the bending stress of tooth root of planetary gear and half-shaft gear is reduced by 4.40% and 5.62% respectively. Finally， finite element simulation analysis is used to verify that the fatigue life of the modified differential gear meets the requirement， and the bench experiment is carried out to verify.